MANAGEMENT OF BAGA UTSAHA PADRUWEN OF TRADITIONAL VILLAGE (BUPDA) IN ECONOMIC EMPOWERMENT OF TRADITIONAL LAW COMMUNITIES IN BALI - I Wayan Suarjana; I Made Suwitra; I Nyoman Sujana (Journal Equity of Law and Governance, 2024)
Traditional Villages in Bali have the task of realizing Traditional Village customs which include tranquility, prosperity, happiness, and peace in life and the future. Bali Province Regional Regulation No. 4 of 2019 in conjunction with Bali Province Regional Regulation No. 4 of 2022 is one answer and solution to this task. It contains the ideology and basic framework for the governance of Traditional Villages in Bali and the economic system of Traditional Villages in Bali. It is also a basic strategy for strengthening the existence and role of Traditional Villages. Based on these conditions, the legal issues raised in this research are to analyze (1) the nature of Traditional Village-Owned Enterprise (referred to as BUPDA) management arrangements in Bali Province; (2) the effectiveness of Bali Province Regional Regulation No. 4 of 2019 in conjunction with Bali Province Regional Regulation No. 4 of 2022 in regulating the management of BUPDA in Bali Province; and (3) a BUPDA management model that can improve the welfare and economic independence of traditional law communities in Bali. The research method used is an empirical legal research method. The results of the research show that (1) The nature of BUPDA plays a role in preserving the continuity, preservation of customs, traditions, arts and culture, and local wisdom in Bali and can improve the welfare and independence of Traditional Villages in Bali; (2) The effectiveness of Bali Province Regional Regulation No. 4 of 2019 in conjunction with Bali Province Regional Regulation No. 4 of 2022 or the small number of BUPDA formations in Traditional Villages is also caused by not all factors such as law enforcement, legal quality, and the suitability of regional regulations to local needs and conditions in each district/city which can influence the effectiveness of implementing regional regulations regarding BUPDA; and (3) The BUPDA management model in Bali by integrating the components of cultural capital, economic capital, social capital, religious capital, and technology/IT capital as a hybrid institutional model. BUPDA governance needs to pay attention to cultural, social, religious, and technological aspects in developing the economy of Traditional Villages sustainably based on local potential and wisdom.